2023
DOI: 10.1097/01.gox.0000921672.92950.ad
|View full text |Cite
|
Sign up to set email alerts
|

31. Workplace Bias Affecting Applicants to Independent Plastic Surgery Residencies

Abstract: BACKGROUND:The integrated plastic surgery residency match continues to be highly competitive. Every year, some candidates are former NCAA athletes. While it is challenging to balance academic and athletic responsibilities, participation in NCAA sports may be predictive of continued success. This study aimed to evaluate the impact of participation in collegiate athletics on applicant anticipated rank and academic success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, when considering a career in plastic surgery, general surgery trainees report facing backlash in the form of demeaning comments or jokes by faculty (64.1%) or a lack of support altogether (20.5%). 24 In reality, plastic surgeons are involved in a broad range of aesthetic and reconstructive procedures working from head-to-toe with skin, soft tissue, bone, and visceral organs. As excellent technicians, plastic surgeons perform everything from laparoscopic abdominal wall surgery to liver transplant anastomoses and jejunal esophageal reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when considering a career in plastic surgery, general surgery trainees report facing backlash in the form of demeaning comments or jokes by faculty (64.1%) or a lack of support altogether (20.5%). 24 In reality, plastic surgeons are involved in a broad range of aesthetic and reconstructive procedures working from head-to-toe with skin, soft tissue, bone, and visceral organs. As excellent technicians, plastic surgeons perform everything from laparoscopic abdominal wall surgery to liver transplant anastomoses and jejunal esophageal reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…research productivity, and enrollment in a top-tier medical school as pivotal contributors to a successful integrated match. 3,[5][6][7][8][9][10][11][12] Although there exists literature on achieving a successful independent match, 2,3,[12][13][14][15][16][17] the recent shift toward integrated programs necessitates updated insights. It is imperative to determine if historical success indicators still apply and to understand the program leadership's vision for the future of independent track programs.…”
mentioning
confidence: 99%
“…Previous research has shown that the ChatGPT produces accurate and reproducible outcomes in both the fields of surgery and robotics 4 7 . There is also evidence that ChatGPT can be used as a source of therapy 8 . Some writers claimed that ChatGPT may be broadly utilized in surgical examinations, from text generation to data extraction and even clinical decision-making 9 .…”
mentioning
confidence: 99%
“…There are numerous examples of misleading information generated by the AI model. As a result, the ChatGPT is a human-generated AI-based technology that may produce incorrect information when trained with biased data 2 , 8 .…”
mentioning
confidence: 99%